INVESTIGATION OF THE EFFECTS OF THE ADDITION OF TITANIUM DIOXIDE (TiO2) NANOPARTICLE FUEL ADDITIVE IN COTTON BIODIESEL ON ENGINE PERFORMANCE - MEHMET CELIK; CIHAN BAYINDIRLI (Journal of Engineering Studies and Research, 2024)
The importance of renewable fuels as an alternative to fossil fuels is increasing due to environmental problems such as the decrease in the reserves of fossil fuels, their presence in certain regions, air pollution and global warming. Two important parameters of biodiesel fuel, which is one of these fuel types, such as high viscosity and density, negatively affect its use. One of the ways to overcome this negative situation is to improve the fuel properties by adding nano fuel additives into biodiesel. In this study, titanium dioxide nano fuel additive was added to biodiesel obtained from cottonseed oil at the rates of 50 ppm and 75 ppm. Specific fuel consumption, brake thermal efficiency and cylinder pressure values, which are the basic performance parameters of the fuel mixtures, were determined in a single cylinder engine at 1800 rpm at 4 different engine loads. According to C100 fuel SFC decreased by 5.03% and 6.29% at 10 Nm load, respectively in CTi-50 and CTi-75 fuels. This improvement rate was 8.73% and 12.58% at 40 Nm load. BTE increased by 8.97% and 13.17% with NPs additives. Thanks to the thermophysical properties of the titanium dioxide fuel additive, the combustion reaction has improved and cylinder pressure increased. It was determined in the study that it positively affected the engine performance and fuel economy.